Studies in Syriac Spirituality - Thonippara, Francis (Asian Horizons, 2009)
Studies in Syriac Spirituality - By Sebastian Brock Dharmaram Publications, Dhatmaram College, P.O., Bangalore-560029; Pages XU+273, PriceRs,160; USD16. Revised, enlarged and updated edition